2004
DOI: 10.1093/annhyg/meg081
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Keratin Protein in a Tape-stripped Skin Sample from Jet Fuel Exposed Skin

Abstract: Chemical contaminants or their metabolites may bind to and react with keratin proteins in the stratum corneum of the skin. Here, we present a tape-stripping method for the removal and quantification of keratin from the stratum corneum for normalization of extracted concentrations of naphthalene (as a marker for jet fuel exposure) from 12 human volunteers before and after exposure to jet fuel (JP-8). Due to the potential for removal of variable amounts of squamous tissue from each tape-strip sample, keratin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In contrast to these studies, Cathepsin-D (CATD) could not be identified from our data. The recorded proteomic profile is in line with that observed from the skin surface 18 , 19 , with cytokeratins as dominant protein species. These components make up approximately 35% of the fingermark proteome, whilst the remainder is accounted for by an array of antibiotic proteins as well as secreted blood proteins 22 26 .…”
Section: Resultssupporting
confidence: 84%
“…In contrast to these studies, Cathepsin-D (CATD) could not be identified from our data. The recorded proteomic profile is in line with that observed from the skin surface 18 , 19 , with cytokeratins as dominant protein species. These components make up approximately 35% of the fingermark proteome, whilst the remainder is accounted for by an array of antibiotic proteins as well as secreted blood proteins 22 26 .…”
Section: Resultssupporting
confidence: 84%
“…For each worker, body regions sampled included three of the following body parts: forehead, neck, shoulders, arms, hands, legs, knees, feet, and buttocks. Samples were analyzed by gas chromatography–mass spectrometry (GC-MS) (Chao and Nylander-French 2004). The amount of naphthalene removed with the three successive tape-strip samples was adjusted for the surface area of the particular region sampled in order to estimate the regional dermal exposure to naphthalene.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we examined the contributions of dermal and inhalation exposure to naphthalene, as a marker for JP-8 exposure (Chao et al 2005; Chao and Nylander-French 2004; Egeghy et al 2003; Serdar et al 2003, 2004), to the levels of urinary 1-naphthol and 2-naphthol in U.S. Air Force (USAF) fuel-cell maintenance workers. We demonstrate, using multiple linear regression analyses, that both dermal and inhalation exposure to JP-8 significantly contribute to urinary 1-naphthol and 2-naphthol levels.…”
mentioning
confidence: 99%
“…Protein concentration was determined using the Bradford method with bull serum albumin as standard. 23 Proteins (30 µg) from each samples were loaded on a 12% sodium dodecyl sulfonate-polyacrylamide gel and transferred to a nitrocellulose membrane at 80 mA for 2 h in a water-cooled transfer apparatus. The membrane was pre-incubated in blocking buffer [Tris-buffered saline (TBS) containing Tween and 5% non-fat dried milk] for 2 h at room temperature and then probed with a primary antibody (1:200 diluted in blocking buffer) overnight at 4℃.…”
Section: Methodsmentioning
confidence: 99%